Impacts of geological store uncertainties on the design and operation of flexible CCS offshore pipeline infrastructure. (September 2016) - Sanchez Fernandez, Eva; Naylor, Mark; Lucquiaud, Mathieu; Wetenhall, Ben; Aghajani, Hamed; Race, Julia; Chalmers, Hannah
Highlights: CO2 pipeline transportation infrastructure is analysed in a context of flow variability and geological store performance uncertainty. Storage site operational conditions are limited by the proximity of the wellhead conditions to the CO2 vapour-liquid equilibrium line. Storage site operational conditions are also limited by the maximum fluid velocities inside the well. Uncertainty in storage site properties might affect the ability of the storage site to accommodate variations in CO2 flows. Site screening can be applied to identify sites which are more flexible in terms of uncertainty in store performance. Abstract: Planning for Carbon Capture and Storage (CCS) infrastructure needs to address the impact of store uncertainties and store flow variability on infrastructure costs and availability. Key geological storage properties (pressure, temperature, depth and permeability) can affect injectivity and lead to variations in CO2 flow, which feed back into the pipeline transportation system. In previous storage models, the interface between the reservoir performance and the transportation infrastructure is unclear and the models are unable to provide details for flow and pressure management within a transportation network in response to changes in the operation of storage sites. Variation in storage demand due to daily and seasonal variations of fossil fuels uses and by extension CO2 flow is also likely to influence transportation infrastructure availability and the capacity to deliver. This work evaluates, at the level of infrastructure planning, the impact of geological uncertainty on CCS pipeline transportation and injection infrastructure. The analysis presented shows how to consider uncertainty in store properties in combination with CO2 flow variability to estimate the likely impact on pipeline infrastructure design. The operational envelope of the storage site infrastructure is estimated by combining the Darcy flow analysis of simple reservoir models with rigorous process simulation of the storage site wells. The proximity of wellhead conditions to the CO2 equilibrium line and the maximum velocities inside the well constrain the operational envelope of the storage site and limit the ability of the storage site infrastructure to handle CO2 flow variation. These factors, which are significantly influenced by variations in subsurface conditions, have also an impact on the design of the offshore pipeline infrastructure, needing to accommodate changes in pressure delivery requirements. Based on the evaluation of examples developed for different offshore transportation scenarios relevant to the United Kingdom, detailed insight on the expected impacts of store properties on pipeline transportation infrastructure design and operation is provided. For instance, it is found that enabling storage site flexibility is simpler in stores with an initial pressure above 20 MPa. Given reductions in reservoir permeability, the requirements for pressure delivery are strongly dependent on the store temperature. Although the analysis is performed for specific geological characteristics in the North Sea the evaluation methodology is transferable to other locations and can be used for site screening to identify sites which are more flexible in terms of uncertainty in store performance.